Effect of amphiphilic ionic liquids on the colorimetric properties of polyketides colorants - Veríssismo, Nathalia V. [UNESP] (2022)
Consumers are currently pressuring the food industries to replace synthetic colorants with their natural counterparts. However, natural colorants still represent less than a third of food coloring additives, as they are more difficult to produce and present application issues due to their lower stability. To find surfactants compatible with natural colorants, this study evaluated the effect of amphiphilic ionic liquids (ILs) aqueous solutions on the colorimetric properties of polyketides colorants (yellow-orange and red color) produced by Talaromyces amestolkiae. Only the IL n-alkyl-3-methylimidazolium bromide ([Cnmim]Br with n = 10) at 2.5 mM preserved the colorimetric and fluorescence characteristics of the fungal colorants, while the other surfactants [e.g., [Cnmim]Br with n = 12, 14, and 16, tributyl-tetradecylphosphonium chloride ([P4,4,4,14]Cl), and cetyltrimethylammonium bromide (CTAB)] altered them. Fluorescence was more sensitive to the effect of ILs than their color and absorbance. Furthermore, the red colorant was more affected by the ILs than the yellow-orange chromophores. Hence, this work shows that formulations with [C10mim]Br (up to 2.5 mM) can preserve the properties of T. amestolkiae polyketides colorants, while the other ILs can be used as additives to modulate their color and fluorescence for biosensing applications.